Solubility Enhancement of Posaconazole: A Mixed Solvency Approach Using Urea and Xylenesulfonate - Jaiswal, Abhishek (International Journal of Pharmaceutical & Biological Archive, 2025)
Posaconazole, a broad-spectrum antifungal agent belonging to the triazole class, exhibits poor aqueous solubility, limiting its oral bioavailability and therapeutic effectiveness. As a BCS class II drug, its absorption is dissolution-rate limited, presenting significant challenges in formulation development. This study explores the potential of a mixed solvency approach employing urea and sodium xylenesulfonate (SXS) as synergistic hydrotropic agents to enhance the solubility of posaconazole. A systematic methodology was adopted, beginning with the selection and optimization of solvent concentrations through factorial design, followed by equilibrium solubility studies, Fourier-transform infrared spectroscopy (FTIR) spectroscopy for compatibility analysis, and in vitro dissolution testing. FTIR and differential scanning calorimetry (DSC) analyses confirmed the absence of chemical interactions and indicated physical compatibility between the drug and excipients. The optimized formulation demonstrated a significant increase in solubility compared to pure drug and individual solubilizers, with no degradation observed under stability testing conditions. In vitro dissolution studies revealed enhanced drug release profiles in phosphate buffer (pH 6.8), suggesting improved absorption potential. The mixed solvency technique, which utilizes non-toxic, pharmaceutically acceptable solubilizers in combination, presents a cost-effective, scalable, and regulatory-compliant solution for poorly soluble drugs. The findings of this study establish the scientific rationale and practical applicability of using urea and SXS in combination to overcome solubility limitations of posaconazole, providing a promising strategy for future formulation development of BCS class II compounds.